APOE Genotype and Nonrespiratory Sleep Parameters in Cognitively Intact Older Adults. Issue 8 (6th May 2017) - Spira, Adam P; An, Yang; Peng, Yu; Wu, Mark N; Simonsick, Eleanor M; Ferrucci, Luigi; Resnick, Susan M
Abstract: Study Objectives: The apolipoprotein E (APOE) Ɛ4 allele increases Alzheimer's disease (AD) risk and has been linked to a greater risk of sleep-disordered breathing. We investigated the association of APOE genotype with nonrespiratory sleep parameters. Methods: We studied 1264 cognitively normal participants in the Baltimore Longitudinal Study of Aging (mean = 57.5 ± 16.1 years, range 19.9–92.0, 48.2% women, 19.8% African American) with APOE genotyping and self-reported sleep duration (≥9, 7 or 8, ≤6 hours), difficulty falling/staying asleep, and napping. We compared Ɛ4 carriers with all noncarriers and compared persons at reduced (Ɛ2/Ɛ2 or Ɛ2/Ɛ3) or elevated AD risk (≥1 Ɛ4 allele) with those neutral for AD risk (Ɛ3/Ɛ3). Results: In fully adjusted models, those with ≥1 Ɛ4 allele had a greater odds of being in a shorter sleep duration category compared to all noncarriers (odds ratio [OR] = 1.41, 95% confidence interval [CI] 1.06, 1.88) and Ɛ3/Ɛ3 carriers (OR = 1.43, 95% CI 1.06, 1.92). Compared to Ɛ3/Ɛ3 carriers, Ɛ2/Ɛ2 or Ɛ2/Ɛ3 carriers had a lower odds of reporting napping (OR = 0.64, 95% CI 0.43, 0.96). Among participants aged ≥50 years, sleep duration findings remained and Ɛ4 carriers had a greater odds of trouble falling/staying asleep than noncarriers (OR = 1.49, 95% CI 1.02, 2.17). We found some evidence for stronger associations of Ɛ4 with sleep duration among African Americans. Conclusions: Self-reported sleep duration, napping, and trouble falling/staying asleep differ by APOE genotype. Studies are needed to examine whether APOE promotes AD by degrading sleep and to clarify the role of race in these associations.